Wage Policy and Fiscal Sustainability in Benin - Lundgren, Charlotte (Washington, D.C. : International Monetary Fund, 2010)
This paper analyzes the impact of Benin's public wage policy on medium and long-term fiscal and debt sustainability. The main findings are that if the wage bill continues to increase in line with recent trends, debt and fiscal sustainability could be compromised by excessive deficits or by crowding out growth-enhancing public investment. The study shows that with fiscal policy guided by targets aimed at maintaining debt sustainability, population growth, and the intent to progress towards the Millennium Development Goals, there will be little space for civil service pay increases. Limiting wage bill increases to maintain fiscal sustainability is only a first step in the authorities' broader objective of reforming the civil service.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet